Effectiveness of AI-Based Smart Agriculture Innovation Communication Through the Agrimind Application in Increasing Young Generation’s Interest in Farming - Mohammad Rifky; Eli Purwati; Deny Wahyu Tricana; Saba Mehmood; Wasim Raza (Unversitas Muhammadiyah Mataram, 2026)
The low interest among the younger generation in entering the agricultural sector, as well as the challenges of farmer succession in Indonesia, are the primary issues underlying this study. This study aims to analyze the effectiveness of communicating smart agriculture innovations based on artificial intelligence (AI) through the Agrimind application in increasing young people’s interest in the agricultural sector. This study employs a quantitative descriptive approach, with data collected via a questionnaire administered to 140 respondents from the younger generation in Ponorogo Regency. The collected data was subsequently processed using descriptive statistical analysis methods and tested for validity and reliability. The findings indicate that 70% of respondents support the implementation of modern technology and AI-based training for young farmers. Respondents believe that the use of the Agrimind application can help improve efficiency, attract the interest of young farmers, and strengthen collaboration between senior farmers and the younger generation who are tech-savvy. These findings demonstrate that AI-based agricultural innovation communication holds significant potential for transforming the younger generation’s perception of the agricultural sector, improving farmers’ work efficiency, and strengthening farmer succession in the digital era.